Point-of-Care Ultrasound Diagnosis of Diaphragmatic Hernia in an Infant With Respiratory Distress. Issue 10 (October 2016) - Rankin, Jessica H.; Elkhunovich, Marsha; Seif, Dina; Chilstrom, Mikaela
Abstract : Abstract: Neonatal respiratory distress is an emergent condition with a wide differential diagnosis. A 12-day-old newborn presented to the emergency department in respiratory distress. Point-of-care ultrasound allowed clinicians to rapidly exclude cardiac disease and pneumothorax as possible causes of the patient's respiratory distress, and expedited the identification of congenital diaphragmatic hernia. The ultrasound findings and technique, epidemiology, pathophysiology, and radiological diagnosis of congenital diaphragmatic hernia are reviewed. Abstract : Supplemental digital contents are available in the text.